The great guide what David Hume can teach us about being human and living well - Baggini, Julian (Princeton University Press, 2021)
Provides an account of how Hume's thought should serve as the basis for a complete approach to life. Baggini interweaves biography with intellectual history and philosophy to give us a complete vision of Hume's guide to life. He follows Hume on his life's journey, literally walking in the great philosopher's footsteps as Baggini takes readers to the places that inspired Hume the most, from his family estate near the Scottish border to Paris, where, as an older man, he was warmly embraced by French society. Baggini shows how Hume put his philosophy into practice in a life that blended reason and passion, study and leisure, and relaxation and enjoyment. This book includes 145 Humean maxims for living well, on topics ranging from the meaning of success and the value of travel to friendship, facing death, identity, and the importance of leisure. --From publisher description.